Studi Timbulan Sampah dan Desain Tempat Penampungan Sementara saat Kondisi Pandemik Covid-19 di Lingkup Kampus: Studi Kasus di Universitas Muhammadiyah Kendari - La Ode Muhamad Said; Sumarlin Sumarlin; Wa Ndibale; Eka Dian Srikandi; Moch. Assidieq; Ilham Ilham; Dwiprayogo Wibowo (Universitas Andalas, 2021)
The case of garbage accumulated during the COVID-19 pandemic in front of the University of Muhammadiyah Kendari (UM Kendari) Campus showed a drastic change in the volume of waste accumulation. The emergence of lockdown regulations and online learning processes show a small amount of garbage collected, but from the other side, there needs to be anticipation when starting normal lectures. Based on these conditions, this study aims to determine the amount of waste generated by the UM Kendari campus during the covid-19 pandemic and to plan a temporary disposal site (TPS) for waste in accordance with technical standards. The method used in this study is a statistical analysis to calculate waste generation, at the TPS location in front of the Kendari UM campus. The data required include volume and weight of waste, the composition of waste, profile data of UM Kendari, buildings, students, lecturers, staff and the surrounding community as well as other supporting data for waste management. The results showed that the waste in the UM Kendari campus environment consisted of several compositions of organic waste 51.60%, inorganic waste 48.36%, B3 waste 0.16%. The planned waste TPS adopts a sorting system method based on source, semi-fixed laying with structural components consisting of; 3 partitions bucket/bin trash can made of fibre/iron plate, 3 compartments for bin holder made of bricks. Effective dimensions of bucket/bin 1.0 m × 0.5 m × 1.0 m; and dimensions of the seat body 2.16 m × 1.38 m × 1.29 m; while the dimensions of the TPS unit area are 3.16 m × 2.88 m. Keywords: Garbage, Kendari University, COVID-19, campus, Waste Collection Point (TPS) ABSTRAK Kasus penumpukan sampah selama pandemi COVID-19 di depan Kampus Universitas Muhammadiyah Kendari (UM Kendari) menunjukkan perubahan drastis dalam volume akumulasi sampah. Munculnya peraturan lockdown dan proses pembelajaran online menyebabkan jumlah sampah yang terkumpul menjadi sedikit, namun di sisi lain, perlu ada antisipasi saat memulai perkuliahan normal kembali. Berdasarkan kondisi tersebut, penelitian ini bertujuan untuk menentukan jumlah sampah yang dihasilkan oleh kampus UM Kendari selama pandemi covid-19 dan merencanakan tempat pembuangan sementara (TPS) untuk sampah sesuai dengan standar teknis. Metode yang digunakan dalam penelitian ini adalah analisis statistik untuk menghitung generasi sampah, di lokasi TPS di depan kampus UM Kendari. Data yang diperlukan meliputi volume dan berat sampah, komposisi sampah, data profil UM Kendari, bangunan, mahasiswa, dosen, staf, dan masyarakat sekitar serta data pendukung lainnya untuk pengelolaan sampah. Hasil penelitian menunjukkan bahwa sampah di lingkungan kampus UM Kendari terdiri dari beberapa komposisi sampah, yaitu sampah organik 51,60%, sampah anorganik 48,36%, dan sampah B3 0,16%. TPS sampah yang direncanakan mengadopsi metode sistem pemilahan berdasarkan sumber, penempatan semi-fiks dengan komponen struktural yang terdiri dari; 3 ember/tempat sampah berbahan serat/lembaran besi, 3 kompartemen untuk penahan ember yang terbuat dari bata. Dimensi efektif ember/tempat sampah adalah 1,0 m × 0,5 m × 1,0 m; dan dimensi tubuh tempat duduk adalah 2,16 m × 1,38 m × 1,29 m; sementara dimensi area unit TPS adalah 3,16 m × 2,88 m. Kata Kunci: Sampah, UM Kendari, covid-19, kampus, TPS